The state of S100-positive glia and the effect on it on the GABA-benzodiazepine receptor agonist, carbacetam, in diabetic retinopathy (Ukrainian Journal of Ophthalmology, 2024)
Purpose: To determine the state of S100-positive glia and the effect on it of the gamma-aminobutyric acid (GABA)-benzodiazepine receptor agonist, carbacetam, in early experimental diabetic retinopathy (DR).Material and Methods: DR was induced in 30 Wistar male rats (age, 3 months) by single intraperitoneal injection of 50 mg streptozotocin (STZ)/ kg body weight. These were assigned to two treatment groups (30 units of insulin only and 30 units of insulin plus carbacetam at a dose of 5 mg/ kg body weight in 0.5 mL of saline, respectively) and a control group of untreated diabetic rats, of 10 animals each. In addition, five intact animals were used to assess the retina at baseline conditions. Mouse anti-S100 protein monoclonal antibodies (Thermo Fisher Scientific) were used for immunohistochemical studies.Results: In the intact retina, there was S100-positive staining in multiple polymorphous cells in the inner nuclear layer (INL) and glial fibers surrounding ganglion neurons like a collar. The intensity of S100 staining of Müller cells significantly increased, and their long radial processes were clearly visualized in early untreated DR. Particularly, intensive staining was observed in the outer nuclear layer (ONL), at the junction of this layer with the rod and cone layer, and in the ganglion layer. On day 28 of the experiment, microaneurysms were observed in the inner retina, with high S100 staining intensity in fibers which adhered to them. Animal treatment with insulin only resulted in a reduction in S100 staining intensity, whereas animal treatment with insulin plus carbacetam inhibited S100 protein expression and prevented the development of retinal microaneurysms, with only solitary Müller cells in the INL and the plexus in the ganglion cell layer exhibiting weak staining.Conclusion: The GABA-benzodiazepine receptor agonist, carbacetam, was found to have an inhibiting effect on the expression of S100 protein and formation of retinal microaneurysms in early DR associated with STZ-induced diabetes in rats.
Keywords: diabetic retinopathy; neurodegeneration; benzodiazepine receptors; immunohistochemistry; streptozotocin; Müller cells; S100 protein; retina